Energy-Efficient Enhanced Hierarchical Routing Chain Based Clustering for Wireless Sensor Networks - et. al., Vidhya G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Networks (WSN) constitute a wide range of applications. In most applications, sensor nodes are distributed in harsh environments and WSN nodes are power-limited, so once installed it will be difficult to charge those sensor nodes. In this article, combined with clusters, we propose a routing scheme that saves energy. First, the entire surface of the sensor is divided into parts, and then the sensor is divided by weighing the elements. Each section selects a Cluster Head (CH).Clustering is one of the common methods to maximize energy production. All sensor hubs are assembled into a number of groups in the clustering technique and each group is assigned a group head called the Cluster Head (CH). The CH absorbs high energy as they are responsible for data processing and data transmission compared to the remaining Sensor Nodes (SNs). The heads of the cluster are usually overwhelmed with a large number of sensing nodes, resulting in faster death. We propose an enhanced hierarchical routing chain-based clustering (EHRCC) algorithm based on the LEACH algorithm. The EHRCC algorithm uses E-LEACH, PEGASIS-E, LEACH-1R PEGASIS and P-LEACH algorithm to investigate the creation of clusters, cluster head choice, chain creation, as well as the data transmission mechanism. Simulation results show that, EHRCC is better consumption of energy compared to HEED, E- LEACH,E- PEGASIS In addition, we evaluate the impact of various network parameters on network efficiency and further improve its performance.